The Effect of Anaerobic Composting Method of Coffee Waste on The Growth of Robusta Coffee Seedlings (Coffea canephora L.) - Dewi Rezki; Warnita; Supriyanto; Niken Adrika Susanti; Edwin; Atika Mulia Chandra (Jurusan Budidaya Perkebunan, 2024)
Coffee is one of the plantation commodities that has significant economic value. A factor that needs to be considered in coffee plant cultivation is good planting media composition. This study aims to determine the effect of planting media composition on the growth of robusta coffee seedlings. This study used a Completely Randomized Design with treatments M0= Soil: 100%, M1= Soil: 50% + Coffee Husk Compost: 25% + Rice Husk: 25%, M2= Soil: 25% + Coffee Husk Compost: 50% + Rice Husk: 25%, M3= Soil: 25% + Coffee Husk Compost: 25% + Rice Husk: 50%. The analyses conducted were compost analysis and initial and post-incubation soil analysis. Observation data were analyzed using the F test followed by DNMRT at the 5% level. The research results show that the provision of coffee husk compost and rice husks affects the chemical properties of the soil and the growth of coffee seedlings. The planting media composition of Soil: 25% + Coffee Husk Compost: 50% + Rice Husk: 25% proved to increase the pH of the planting media from 5.5 to 6.6, increase in total N-value from 0.2% to 0.5%, available P from 18.6 ppm to 38.5 ppm and the soil CEC from 7.6 me/100g to 36.6 me/100g. This planting media composition also makes it possible to enhance the growth of robusta coffee seedlings in plant height, stem diameter, number of leaves, leaf width, and root volume. Thus, this planting media composition is a suitable medium for the growth of robusta coffee seedlings.